Dialogic Management in Adult Education - Itxaso Tellado (Adult Education Research Conference, 2007)
Dialogic management in adult education promotes an outstanding organizational practice for adult learning centers. The involvement of learners in decision making teams is essential to the success of shared governance and other participative structures and, is one of the aspects that explain the higher levels of participation in the school.